Can site and landscape‐scale environmental attributes buffer bird populations against weather events?. Issue 9 (2nd April 2014) - Newson, Stuart E.; Oliver, Tom H.; Gillings, Simon; Crick, Humphrey Q. P.; Morecroft, Michael D.; Duffield, Simon J.; Macgregor, Nicholas A.; Pearce‐Higgins, James W.
<x xml:space="preserve">Abstract</x> Projected impacts of climate change on the populations and distributions of species pose a challenge for conservationists. In response, a number of adaptation strategies to enable species to persist in a changing climate have been proposed. Management to maximise the quality of habitat at existing sites may reduce the magnitude or frequency of climate‐driven population declines. In addition large‐scale management of landscapes could potentially improve the resilience of populations by facilitating inter‐population movements. A reduction in the obstacles to species' range expansion, may also allow species to track changing conditions better through shifts to new locations, either regionally or locally. However, despite a strong theoretical base, there is limited empirical evidence to support these management interventions. This makes it difficult for conservationists to decide on the most appropriate strategy for different circumstances. Here extensive data from long‐term monitoring of woodland birds at individual sites are used to examine the two‐way interactions between habitat and both weather and population count in the previous year. This tests the extent to which site‐scale and landscape‐scale habitat attributes may buffer populations against variation in winter weather (a key driver of woodland bird population size) and facilitate subsequent population growth. Our results provide some support for the prediction that landscape‐scale attributes (patch isolation and area of woodland habitat) may influence the ability of some woodland bird species to withstand weather‐mediated population declines. These effects were most apparent among generalist woodland species. There was also evidence that several, primarily specialist, woodland species are more likely to increase following population decline where there is more woodland at both site and landscape scales. These results provide empirical support for the concept that landscape‐scale conservation efforts may make the populations of some woodland bird species more resilient to climate change. However in isolation, management is unlikely to provide a universal benefit to all species.